A review of the scientific literature as it pertains to Gulf War illnesses. Vol. 7, Depleted uranium - Harley, Naomi H.; Foulkes, Ernest C., 1924-; Hilborne, Lee H., 1956-; Hudson, Arlene; Anthony, C. Ross.; Rand Corporation; National Defense Research Institute (U.S.). Forces and Resources Policy Center; Center for Military Health Policy Research; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 1999)
Because of the metal's density and metallurgical properties, depleted uranium (DU) saw widespread use during the Persian Gulf War in improved armor and antiarmor rounds of increased penetrating power. This report examines the scientific literature regarding possible health effects on U.S. troops of exposure to DU. While very little literature directly addresses DU, a wide body of literature deals with the health effects of natural uranium and enriched uranium. DU is toxicologically identical to natural uranium and radiologically more benign because it is less radioactive. No increase in overall deaths has been observed as a result of exposure to natural uranium in several epidemiological studies. The literature review paid close attention to the ongoing study of a group of Gulf War Veterans who received the highest exposure to DU. Those with embedded fragments have elevated urine uranium levels, but researchers report neither adverse renal effects attributable to DU nor any adverse health effects related to DU radiation.
"National Defense Research Institute."
"This work ... was carried out jointly by RAND Health's Center for Military Health Policy Research and the Forces and Resources Policy Center of the National Defense Research Institute"--Preface.
Includes bibliographical references (p. 103-118).
Also available on the internet via WWW.
Keywords: Chemical agents (Munitions) -- Health aspects; Persian Gulf syndrome -- United States; Persian Gulf War, 1991 -- Health aspects -- United States; Persian Gulf War, 1991 -- Veterans -- Diseases -- United States; Veterans -- Diseases -- United States